Ever true : 150 years of giant leaps at Purdue University - Norberg, John; ProQuest (Firm) (West Lafayette, Indiana : Purdue University Press, 2019)
"In 1869 the State of Indiana founded Purdue University as Indiana's land-grant university dedicated to agriculture and engineering. Today, Purdue stands as one of the elite research and education institutions in the world. Its halls have been home to Nobel Prize- and World Food Prize-winning faculty, record-setting astronauts, laurelled humanists, researchers, and leaders of industry. Its thirteen colleges and schools span the sciences, liberal arts, management, and veterinary medicine, boasting more than 450,000 living alumni. Ever True: Celebrating the First 150 Years of Purdue University by John Norberg captures the essence of this great university. In this volume, Norberg takes readers beyond the iconic redbrick walls of Purdue University's West Lafayette campus to delve into the stories of the faculty, alumni, and leaders who make up this remarkable institution's distinguished history. Written to commemorate Purdue University's sesquicentennial celebrations, Ever True picks up where prior histories leave off, bringing the intricacies of historic tales to the forefront, updating the Purdue story to the present, and looking to the future"--
Includes bibliographical references and index.
Description based on print version record
eBooks on EBSCOhost
Keywords: Purdue University -- History; Purdue University; EDUCATION / Higher; HISTORY / United States / State & Local / Midwest (IA, IL, IN, KS, MI, MN, MO, ND, NE, OH, SD, WI); History